KEANEKARAGAMAN JENIS ANGGREK PADA BEBERAPA PENANGKARAN DI DESA AMPERA DAN DESA KARUNIA KECAMATAN PALOLO KABUPATEN SIGI - Fandani, Hertin Setia; Mallombasang, Sri Ningsih; Korja, i Nengah (Universitas Tadulako, 2018)
Forests are generally known as a resource that is very unique because of the processes of interaction between various constituent components. Every form of forest ecosystem has different capabilities in terms of meeting their needs for environmental conditions including climate. Indonesia is a country that holds the wealth of the largest orchid germplasm in the world. Indonesia has around 6,000 species out of 26,000 world orchid plants. The purpose of the study was to determine the species diversity of orchids in the captivity of Ampera and Karunia Villages, which are found in 6 Sigi Public High Schools and one of the private captives owned by Mr. Sardin. Data collection techniques are carried out in two ways, namely primary data and secondary data. To find out the types of natural orchids found in the captivity of Ampera Village and Karunia Village, Palolo District, Sigi District, descriptive data analysis was used. While to find out the diversity of natural orchid species analyzed using the Shannon-Wienner (H ') Diversity formula. The results showed that the diversity of natural orchid species in the middle of Ampera and Karunia villages was high, with a species diversity index (H ') of 3.25.Keywords: analysis diversity index